The Role of Fiscal Policy in Sustainable Stabilization : Evidence From Latin America - Schwartz, Gerd (IMF Working Papers; Working Paper ;, 1997)
This paper reviews the role of fiscal policy in a number of stabilization programs in Latin America since the early 1980s. The paper highlights the importance of sustainable fiscal adjustment in stabilization efforts, and discusses the main issues that arise in this context. By reviewing the Latin American experience, it is argued that responsibility for failed stabilization attempts can be traced to four main factors: inconsistent policy mixes; excessive reliance on temporary factors of improvement in the fiscal accounts; failure to implement fundamental fiscal reforms; and lack of complementary structural reforms.